A New Model of Packet tracking Using The TSP Algorithm Method - Hardi, Richki; Nanna Suryana Herman; Naim Che pee (Mulia International Journal in Science and Technical, 2019)
The packet tracking system becomes essential for the sender of the packet because, with this system, the sender can know the whereabouts or position of the package being sent. If there is a delay in delivery, the sender can also find out the cause of the delay, and it could be due to traffic, wrong address, natural disaster, or other problems. More than that, this system can determine the optimal route to be passed, namely by testing and moving several paths so that with all the possibilities that there will get the optimal path. The purpose of this study is to provide a model and find out the optimal way that is feasible to take in package delivery. The method applied in this research is to use the TSP algorithm, which is an algorithm that tries all possible routes to get the optimal path. The research area will be applied to the Aceh area, and also a request from one of the national shipping companies in Indonesia, Pos. This system will be built based on the web so that the results displayed can be reached by all areas that are connected to the internet. It is hoped that this model and system that will be built can become a reference and reference for other researchers.